The Real Solutions to the Ignored Prison Overcrowding Problem - Hamja, Hamja; Ravena, Dey; Sudiro, Amad; Nunna, Bhanu Prakash (Unissula, 2025)
This study aims to analyze prison overcapacity for concrete and operational solutions. This study used a normative research approach. The author's research results recommend adaptive solutions to the problem of overcrowding, including measuring the improvement of the process of making prison policies and crime prevention in the form of various restorative and rehabilitative regulations such as rehabilitation programs for drug offenders, the application of monetary penalties in lieu of imprisonment, the implementation of open prisons, and the implementation of social control laws; evaluating various guidance efforts that have been carried out to reduce the number of recidivism as a major contributor to overcrowding in addition to prison policies and the judicial process; and deepening the understanding of restorative and rehabilitative efforts in the form of vocational, guidance, job coaching, reintegration in society, as well as public perceptions of prisoners as an implicit driving factor towards repeat crimes. The novelty of this study lies in its integrated perspective, which connects prison overcapacity with the broader need for systemic reform in correctional philosophy.